TDP-43 accumulation in inclusion body myopathy muscle suggests a common pathogenic mechanism with frontotemporal dementia. Issue 10 (16th September 2008) - Weihl, C C; Temiz, P; Miller, S E; Watts, G; Smith, C; Forman, M; Hanson, P I; Kimonis, V; Pestronk, A
Abstract : TAR DNA binding protein-43 (TDP-43) is found in ubiquitinated inclusions (UBIs) in some frontotemporal dementias (FTD-U). One form of FTD-U, due to mutations in the valosin containing protein (VCP) gene, occurs with an inclusion body myopathy (IBMPFD). Since IBMPFD brain has TDP-43 in UBIs, we looked for TDP-43 inclusions in IBMPFD muscle. In normal muscle, TDP-43 is present in nuclei. In IBMPFD muscle, TDP-43 is additionally present as large inclusions within UBIs in muscle cytoplasm. TDP-43 inclusions were also found in 78% of sporadic inclusion body myositis (sIBM) muscles. In IBMPFD and sIBM muscle, TDP-43 migrated with an additional band on immunoblot similar to that reported in FTD-U brains. This study adds sIBM and hereditary inclusion body myopathies to the growing list of TDP-43 positive inclusion diseases.